Hyperuricemia and the gut microbiota: current research hotspots and future trends - Yang, Jingjing; Chen, Jing; Li, Dingxiang; Wu, Qin; Zhang, Yanan; Li, Yujia; Deng, Yihui (Frontiers in Microbiology, 2025)
BackgroundHyperuricemia (HUA), found widely in humans and birds, is a key physiological factor responsible for the development of gout. In recent years, the relationship between the gut microbiota and HUA has garnered significant attention from researchers. This study aims to explore the current research hotspots, knowledge gaps, and future research trends regarding the gut microbiota and HUA.MethodsWe performed a thorough search of the literature on gut flora and HUA published between 2005 and 2024 using the Web of Science and PubMed databases. The resulting data were analyzed using VOSviewer, CiteSpace, and Bibliometrix.ResultsIncluding 735 papers in total, the study found that the number of publications in the subject increased significantly between 2020 and 2024, with 2024 being the year with the highest number of publications. The primary research countries are highlighted as China and the United States, with institutions such as the University of California, San Diego, and Qingdao University making significant contributions. Sanjay K. Nigam and Chenyang Lu have made the most important contributions as authors. Keywords analysis highlighted high-frequency terms including “gastrointestinal microbiome,” “uric acid,” “hyperuricemia,” “inflammation,” “gout,” and “probiotics.” In the visualization map of the keyword timeline, emerging research hotspots include “diets,” “dietary fiber,” “fecal microbiota transplantation,” and “gut-kidney axis.”ConclusionThis study is the first to conduct a quantitative literature analysis in the field of gut microbiota in HUA, revealing that the core research hotspots include disease-related microbiota characteristics, probiotic therapy, microecological intervention, and the gut-distal target organ axis. The emerging hotspots focus on dietary supplementation, fecal microbiota transplantation (FMT) treatment strategies, and in-depth research on the above organ axes. Provide valuable guidance for future research directions.